A fluorescent microsphere-based screen printing fabric anti-counterfeiting pattern and a preparation method thereof

CN122980239APending Publication Date: 2026-10-27WUHAN TEXTILE UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611123276.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]针对现有技术的不足,本发明提供了一种基于荧光微球的丝网印花织物防伪图案及其制备方法,解决了现有纺织品荧光印花过度依赖成膜粘合剂引发的织物物理性能受损,以及静态发光防伪模式仿造门槛较低、缺乏动态验证机制的问题

Benefits of technology

1、本发明通过不含成膜粘合剂的荧光色浆进行印花,并结合织物底涂预处理工艺,使带有富羧基壳层的聚苯乙烯荧光微球直接与底涂层中的碳二亚胺或氮丙啶活性交联基团发生化学偶联,这种依靠界面化学键锚定代替传统高分子成膜粘合剂包裹的固着方式,在保留纺织基材原有孔隙结构与柔软手感的同时,避开树脂膜层对外部溶剂分子渗入以及内部荧光信号释放的物理阻隔,为后续防伪验证阶段的溶剂刺激响应提供相对通畅的物质与光信号传导路径。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122980239A_ABST
    Figure CN122980239A_ABST
Patent Text Reader

Abstract

The present application relates to the field of textile printing and anti-counterfeiting technology, and discloses a silk screen printing fabric anti-counterfeiting pattern based on fluorescent microspheres and a preparation method thereof, which comprises a textile base material, a primer pretreatment layer and an anti-counterfeiting printing layer, wherein the anti-counterfeiting printing layer is formed by printing and baking a resin-free color paste containing carboxyl group-rich high-load polystyrene fluorescent microspheres on the surface; in a dry state, the high-load fluorescent dye inside the microspheres is aggregated and quenched due to excessive local concentration, and the fluorescent signal is significantly inhibited, so that the anti-counterfeiting pattern is in a low-fluorescent hidden state; when wetted by a specific polarity ratio of security verification liquid, the polystyrene matrix is instantaneously and reversibly limited to swell under the restriction of the crosslinked network inside the microspheres, so that the distance between dye molecules is increased, the quenching effect is effectively reduced, and characteristic fluorescence is excited and released. The present application uses interface chemical bonding to replace the traditional physical wrapping of adhesives, and constructs a dynamic and reversible anti-counterfeiting system with solvent stimulation response characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of textile printing and anti-counterfeiting technology, specifically to an anti-counterfeiting pattern for screen-printed fabric based on fluorescent microspheres and its preparation method. Background Technology

[0002] The application of anti-counterfeiting technology in textiles has practical engineering value in brand protection and market traceability. Fluorescent anti-counterfeiting printing, due to its invisibility under normal ambient light and its ability to display preset patterns under specific conditions, has been introduced into the textile printing and dyeing production system. Current fluorescent printing processes usually use screen printing to transfer pigments loaded with luminescent materials to the fabric surface. In actual production, in order to maintain the structural adhesion of fluorescent pigments or luminescent microcapsules after washing and daily friction, existing formulation systems usually mix acrylic or polyurethane polymer resins into the printing pigments as film-forming adhesives.

[0003] This fixation method, which relies on the physical encapsulation of polymer adhesives, has certain limitations in application. After thermosetting, the polymer resin constructs a continuous or semi-continuous film structure on the fabric surface. While this film seals the micropores of the fabric and reduces the material's breathability and feel, it also forms an interface shielding for the fluorescent material encapsulated within. This shielding weakens the efficiency of external excitation energy transfer to the fluorescent material and interferes with the normal release of optical signals. In terms of anti-counterfeiting mechanisms, conventional printing often constructs a unidirectional static ultraviolet light excitation response model. This model relies on excitation and emission at a fixed wavelength, and its mechanism falls within the conventional photoluminescence category. Counterfeiters can replicate similar visual effects by using spectral analysis and reverse mixing of luminescent agents, making it lack dynamic and reversible security barriers when facing multi-level verification requirements.

[0004] In the subsequent evolution of anti-counterfeiting printing technology, exploring fixation methods that break away from traditional adhesive systems and constructing multi-dimensional stimulus-response anti-counterfeiting models have become the direction of technological improvement. This requires establishing a direct chemical connection channel between the luminescent material and the substrate interface without changing the original physical form of the fabric's fiber network. Based on this structure, dynamic response units with microscopic morphological transformation and reversible switching of luminescence state are introduced, thereby providing a technical solution that takes into account both the fabric's performance and high security verification logic. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a screen-printed anti-counterfeiting pattern for fabrics based on fluorescent microspheres and its preparation method. This solves the problems of excessive reliance on film-forming adhesives in existing fluorescent printing of textiles, which leads to damage to the physical properties of the fabrics, as well as the low imitation threshold and lack of dynamic verification mechanisms in static luminescent anti-counterfeiting modes.

[0006] To achieve the above objectives, the present invention provides the following technical solution: Firstly, the present invention provides a screen-printed anti-counterfeiting pattern for fabrics based on fluorescent microspheres, employing the following technical solution: A screen-printed anti-counterfeiting pattern for fabric based on fluorescent microspheres includes a textile substrate, a base coating pretreatment layer bonded to the surface of the textile substrate, and an anti-counterfeiting printing layer bonded to the surface of the base coating pretreatment layer. The anti-counterfeiting printing layer is formed by printing and baking with fluorescent pigment without film-forming binder, and the anti-counterfeiting printing layer contains highly loaded polystyrene fluorescent microspheres, which are chemically cross-linked and anchored to the base coating pretreatment layer or textile substrate. The fluorescent pigment without film-forming binder comprises the following components in parts by weight: 47 to 69 parts of deionized water; Thickener 1 to 3 parts; 30 to 50 parts of high-load polystyrene fluorescent microsphere stock solution with surface-rich carboxyl groups.

[0007] Under normal dry conditions, the fluorescent dye embedded inside the microspheres is in a high-concentration aggregated and quenched state beyond the critical distance, suppressing and concealing the anti-counterfeiting optical signal. When wetted by the security verification liquid, the shell of the high-density polystyrene microspheres undergoes transient confined swelling, breaking the aggregated state of the dye molecules and exciting the release of the corresponding characteristic fluorescent signal.

[0008] By adopting the above technical solution, this application does not add film-forming resin binders to the printing paste, but promotes the fixation of microspheres on the fabric through chemical interfacial reaction, thereby constructing a corresponding solvent-stimulated response anti-counterfeiting system.

[0009] Specifically, the resin-free chemical crosslinking anchoring mechanism in this process is as follows: during the synthesis stage, carboxyl functional groups are introduced into the surface of polystyrene microspheres. After printing, the microspheres undergo high-temperature baking, and the free carboxyl groups on the surface of the microspheres undergo a coupling reaction with the active crosslinking groups in the pretreatment layer of the base coating. Taking the base coating containing a carbodiimide crosslinking agent as an example, the carbodiimide groups are protonated with the carboxyl groups on the surface of the microspheres, promoting the formation of an O-acylurea intermediate. At the baking temperature, this intermediate rapidly undergoes intramolecular rearrangement, forming a stable and irreversible N-acylurea crosslinking network with the carboxyl groups on the surface of the microspheres and the crosslinking agent itself, thereby achieving the firm adhesion of the microspheres to the fabric.

[0010] Due to the formation of the aforementioned network structure, the fluorescent microspheres can still adhere to the fabric surface even after being detached from the polymer adhesive, which to some extent preserves the fabric's own porous structure and feel. The dynamic response mechanism of the microspheres is mainly based on the aggregation quenching of dye molecules and the transient confined swelling behavior of the shell. Under normal conditions, the microspheres contain a high concentration of fluorescent dye, and the distance between dye molecules is lower than the critical distance for initiating energy transfer; their molecular orbital overlap induces a π-π stacking effect.

[0011] At this point, the excitation energy is mostly consumed in the form of non-radiative transitions, causing the fluorescence signal to be quenched, which appears as a concealed pattern on a macroscopic scale. When the surface of the microsphere comes into contact with a safety verification liquid with suitable solubility parameters, solvent molecules penetrate into the polystyrene polymer network. The relaxation of the polystyrene macromolecular chains causes the microsphere volume to expand, i.e., a transient restricted swelling phenomenon occurs. As the microsphere volume expands, the dye molecules embedded inside are affected by spatial isolation, and the intermolecular distance is increased to exceed the quenching critical distance. The original π-π packing state is broken. These free dye molecules will release the corresponding characteristic fluorescence under photoexcitation. During the solvent evaporation process, the microsphere will gradually shrink and tend to return to a dense state, and the fluorescence will be quenched a second time, thus achieving a reversible verification process.

[0012] Preferably, the surface-rich carboxyl-enriched, highly loaded polystyrene fluorescent microsphere stock solution is polymerized from raw materials comprising the following parts by weight: 105 parts of deionized water; Styrene: 11.16 to 11.4 parts; Acrylic acid 0.6 to 0.84 parts; 0.06 to 0.12 parts of fluorescent dye; 0.12 to 0.36 parts of n-hexadecane; Sodium dodecyl sulfate, 0.2 to 0.8 parts; Potassium persulfate 0.06 to 0.18 parts.

[0013] By employing the above technical solution, the copolymerization reaction of styrene and acrylic acid in a predetermined ratio helps to regulate the density of the microsphere skeleton and the distribution density of surface carboxyl groups. The hexadecane in the formulation, as part of the stabilizing system, can suppress the Oswald ripening effect during polymerization, maintain the relative stability of the fine emulsion droplet size, thereby providing space for the encapsulation of fluorescent dyes and reducing the probability of free dye precipitation in the aqueous phase.

[0014] Preferably, the textile substrate is one of pure cotton scourted plain weave, polyester plain weave, or polyester-cotton blend plain weave. The active crosslinking groups contained in the primer pretreatment layer are one of the following: an aqueous multifunctional carbodiimide crosslinking agent or trimethylolpropane-tris(3-aziridinepropionate); The thickener in the fluorescent color paste without film-forming binder is either powdered sodium polyacrylate or sodium alginate. The fluorescent dye is one of rhodamine B base, N,N'-bis(2,6-diisopropylphenyl)-3,4,9,10-perylenetetracarboxylic acid diimide, or pyrene.

[0015] By adopting the above technical solution, the specified carbodiimide or aziridine crosslinking agent has suitable reactivity, which is conducive to coupling with the carboxyl groups on the surface of microspheres under conventional baking conditions. In the color paste system, sodium polyacrylate or sodium alginate replaces the resin binder to play a thickening role, giving the screen printing appropriate rheological properties. Moreover, these water-soluble polymers mostly exist in a discontinuous phase or are washed away during the printing and drying process, reducing the obstruction to the process of the safety verification liquid penetrating into the microsphere shell.

[0016] Preferably, the anti-counterfeiting pattern is used in conjunction with the security verification liquid for anti-counterfeiting verification. The security verification liquid is separate from the pattern product and contains the following components in parts by weight: 20 to 40 parts of ethyl acetate 60 to 80 parts of isopropanol.

[0017] By adopting the above technical solution, the mixed solvent constructed by compounding ethyl acetate and isopropanol exhibits a comprehensive polarity and solubility parameter that tends to induce polystyrene to swell rather than completely dissolve. In this mixed system, the isopropanol component helps to improve the wetting effect of the liquid on the fabric surface, while ethyl acetate tends to penetrate into the polystyrene shell to drive the swelling behavior. The combined effect of the two is beneficial to regulate the time delay of fluorescence signal excitation and the subsequent solvent evaporation and recovery process.

[0018] Preferably, the anti-counterfeiting pattern includes a main anti-counterfeiting area and a homogeneous fluorescence noise calibration area. The minimum line width of the main anti-counterfeiting area is controlled between 0.1 and 0.2 mm, and the homogeneous fluorescence noise calibration area is provided with a reference color block for mapping the decoding rules of numbers, letters, or symbols.

[0019] By adopting the above technical solution, the main anti-counterfeiting area is finely controlled in terms of line width and a homogeneous fluorescence noise calibration area is introduced. This reduces the interference of external stray light or optical brighteners on the microsphere feature fluorescence signal to a certain extent. Combined with the reference color block and specific decoding rules, a logical verification method is added to the visual verification of the anti-counterfeiting pattern.

[0020] Secondly, the present invention provides a method for preparing anti-counterfeiting patterns on screen-printed fabrics based on fluorescent microspheres, using the following technical solution: A method for preparing anti-counterfeiting patterns on screen-printed fabrics based on fluorescent microspheres includes the following steps: S1. Use image processing software to design monochrome or multicolor fluorescent screen printing partition artwork; S2. Apply the primer working liquid to the surface of the textile substrate, and then send it into a hot air setting machine to dry, thus completing the primer crosslinking pretreatment of the textile substrate. S3. Add a thickener to water and stir until it is completely swollen or gelatinized. Then add the high-load polystyrene fluorescent microsphere stock solution with rich carboxyl groups on the surface and continue stirring without adding a film-forming binder to prepare a fluorescent paste without a film-forming binder. S4. The fluorescent pigment without film-forming adhesive is overprinted onto the surface of a textile substrate that has undergone a pre-treatment of cross-linking under a base coating according to the color separation pattern. After printing, the substrate is baked to use heat energy to promote the coupling or cross-linking anchoring reaction of free carboxyl groups on the surface of the microspheres under the action of the active components of the base coating, thereby obtaining a screen-printed anti-counterfeiting pattern for the fabric based on fluorescent microspheres.

[0021] By adopting the above technical solution, the preparation process arranges the active sites of the cross-linking reaction on the side of the fabric base coating. The fabric surface is preloaded with reactive groups by the base coating pretreatment. After entering the baking stage, the thermal conditions cause the microsphere surface and the base coating interface to undergo chemical coupling. This direct anchoring method in a resin-free environment avoids the blockage of light signals or solvent penetration by the film layer in the traditional adhesive adhesion mode, and provides a process basis for preserving the stimulus response characteristics of the anti-counterfeiting pattern.

[0022] Preferably, in S3, the high-load polystyrene fluorescent microsphere stock solution with carboxyl-rich surface is prepared in advance as follows: the fluorescent dye is dissolved in a mixed monomer of styrene and acrylic acid, and n-hexadecane is added and ultrasonically treated to obtain an oil phase; Sodium dodecyl sulfate was added to 100 parts of deionized water and stirred to obtain an aqueous phase; the oil phase was added dropwise to the aqueous phase and homogenized using a high-shear emulsifier to form a fine emulsion system. Under nitrogen protection and mechanical stirring, the system was heated to 70 to 80°C, and potassium persulfate solution dissolved in 5 parts of deionized water was added dropwise. The reaction temperature was maintained and the reaction continued for 6 to 10 hours. After the reaction is completed and cooled, unreacted monomers and free dyes are removed by dialysis, and the solid content is concentrated to 10% to 20%.

[0023] By adopting the above technical solution, the pre-emulsion polymerization method enables monomer droplets to complete the nucleation and polymerization process as independent micro-reaction regions. Acrylic acid in the system tends to participate in the reaction at the oil-water phase interface, which promotes the formation of a certain density of carboxyl enrichment zone on the surface of polystyrene microspheres. Subsequent dialysis treatment to separate free dyes can reduce the risk of free components smudging the fabric background color in subsequent printing processes and maintain the background contrast when the pattern is presented.

[0024] Preferably, in S2, the primer working solution is prepared from 2 to 5 parts by weight of an aqueous multifunctional carbodiimide crosslinking agent or trimethylolpropane-tris(3-aziridinium propionate) and 95 to 98 parts by weight of deionized water. The application method adopts a two-dip, two-roll milling process, with the milling pressure controlled at 0.25 to 0.35 MPa and the slurry yield at 60% to 80%. The drying temperature of the hot air setting machine is 80 to 100°C, and the drying time is 2 to 5 minutes.

[0025] By adopting the above technical solution, the two-dip and two-roll process helps the base coating liquid penetrate into the fabric yarn network. The limited drying temperature range of 80 to 100°C is designed to promote water evaporation to establish a crosslinking agent distribution layer, reduce the phenomenon of premature self-crosslinking or activity decay of crosslinking groups caused by excessive temperature, and thus retain usable interfacial active sites for the subsequent microsphere anchoring reaction.

[0026] Preferably, the specific implementation method in S3 is as follows: first add deionized water, turn on the mechanical stirrer and set the speed to 200 to 400 rpm, add the thickener in batches or continuously within 3 to 10 minutes, continue stirring for 60 to 180 minutes, then add the high-load polystyrene fluorescent microsphere stock solution, adjust the stirrer speed to 500 to 800 rpm at 25°C and continue homogenizing for 30 minutes.

[0027] By adopting the above technical solution, controlling the stirring speed in the early stage of paste preparation and adding thickener in stages to provide a swelling process is beneficial to constructing the initial structural viscosity of the color paste. After the microsphere stock solution is mixed in, the shear force is introduced by increasing the stirring speed, which promotes the dispersion of microspheres in the polymer network formed by the thickener, alleviates the tendency of microsphere particles to agglomerate due to their own gravity or repulsion in the resin-free system, and maintains the operational stability of the color paste system.

[0028] Preferably, S4 is implemented as follows: using a 200 to 400 mesh screen with a screen tension set to 18 to 22 N / cm, and using a polyurethane squeegee to perform overprinting at a squeegee angle of 40 to 50 degrees and a downward pressure of 0.3 to 0.5 MPa; after printing, the screen is sent to a continuous baking oven, and the baking temperature is controlled at 120 to 150°C for 3 to 5 minutes.

[0029] By adopting the above technical solution, the coordinated setting of screen mesh count and printing parameters plays a role in regulating the volume of resin-free pigments penetrating the mesh and depositing onto the undercoated fabric. The set baking temperature range of 120 to 150°C meets the thermodynamic conditions for triggering the chemical bonding between carboxyl groups and crosslinking agents, which is conducive to promoting the interfacial coupling reaction, thereby providing a structural fixation basis for the final printed pattern and improving its wash resistance.

[0030] This invention provides a screen-printed anti-counterfeiting pattern for fabrics based on fluorescent microspheres and its preparation method. It has the following beneficial effects: 1. This invention uses fluorescent pigments without film-forming adhesives for printing, combined with a fabric base coating pretreatment process, to allow polystyrene fluorescent microspheres with carboxyl-rich shells to directly chemically couple with the active crosslinking groups of carbodiimide or aziridine in the base coating. This fixation method, which relies on interfacial chemical bond anchoring instead of the traditional polymer film-forming adhesive, retains the original porous structure and soft feel of the textile substrate while avoiding the physical blockage of the resin film layer on the penetration of external solvent molecules and the release of internal fluorescent signals. This provides a relatively smooth material and light signal transmission path for the solvent stimulation response in the subsequent anti-counterfeiting verification stage.

[0031] 2. This invention utilizes the physical spatial confinement of a polystyrene shell within microspheres in the anti-counterfeiting pattern to maintain a high concentration of fluorescent dye in an aggregated and quenched state. Under normal dry conditions, this maintains optical concealment. When wetted by a security verification solution with specific solubility parameters, the diffusion of the solvent into the polymer network drives the microspheres to undergo transient confined swelling. The increased intermolecular spacing of the dye breaks the original π-π stacking quenching system, thereby exciting characteristic fluorescence. Furthermore, with the natural evaporation of the solvent, the microsphere structure shrinks, causing secondary fluorescence concealment. This process, based on polymer swelling kinetics and dye aggregation state transition, establishes a reversible dynamic response verification mechanism, changing the conventional static anti-counterfeiting mode of UV excitation and raising the technical threshold for counterfeiting to a certain extent.

[0032] 3. This invention, in terms of signal purity control in the anti-counterfeiting system, introduces n-hexadecane through fine emulsion polymerization in the pre-processing stage, combined with a dialysis process, to separate free dye components within the system. This reduces the risk of free pigments smudging the fabric background color during printing applications, thus maintaining background contrast. Based on this material purification, an additional homologous fluorescence noise calibration area and corresponding reference color block mapping decoding rules are added to the anti-counterfeiting printing artwork. This combination of material purification and pattern zoning calibration helps alleviate recognition interference caused by fluorescent whitening agents carried by the fabric itself or stray light from the environment, providing a relatively stable visual comparison benchmark and logical encryption method for anti-counterfeiting information extraction. Attached Figure Description

[0033] Figure 1The graphs show the fluorescence intensity changes based on the physical optical transient response mechanism of Examples 1 to 3 of this invention. Figure 2 The following is a comparison chart of the anti-interference decoding performance of Examples 1 to 3 and Comparative Example 3 of the present invention, wherein (a) is a distribution chart of the decoding success rate of each sample's anti-counterfeiting pattern under strong fluorescent background noise, and (b) is a statistical chart of the average decoding time per test in the corresponding test process. Figure 3 The following is a comparison chart of the physical properties of printed fabrics in Example 1 of the present invention and the comparative examples, wherein (a) is a distribution chart of wet rubbing color fastness grades of each sample, (b) is a comparison chart of air permeability values ​​of corresponding samples, and (c) is a statistical chart of bending stiffness parameter test. Figure 4 The figures show the test results of the fineness of the printed pattern and the edge quality of the present invention. Figure (a) is a comparison of the line width expansion rate of each sample, and Figure (b) is a statistical chart of the coefficient of variation of the edge roughness of each sample. Figure 5 The following is a comparison diagram of the optical response characteristics of the anti-counterfeiting features of Example 1 of the present invention and various comparative examples. Among them, (a) is a trajectory diagram of the change in fluorescence intensity of the anti-counterfeiting pattern of the fabric under different conditions, and (b) is a comparison diagram of the fluorescence surge factor of different samples. Figure 6 The following is a graph showing the performance evolution of Example 1 and the comparative examples of the present invention under continuous water washing and aging. In this graph, (a) is a graph showing the decay trajectory of fluorescence retention rate of each group of samples with the washing cycle, and (b) is a graph showing the trend of decoding success rate of the corresponding sample. Figure 7 The graphs show the peak fluorescence intensity of each group of samples in this invention as a function of irradiation time. Figure 8 This is a scatter plot showing the decay of fluorescence intensity retention rate according to the present invention. Detailed Implementation

[0034] The following is a partial description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative purposes only and are not intended to limit the scope of the invention. In this document, all technical and scientific terms have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. Reagents or instruments used, unless otherwise specified, are all commercially available products.

[0035] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.

[0036] Styrene (CAS: 100-42-5), purity greater than 99.0%.

[0037] Acrylic acid (CAS: 79-10-7), purity greater than 99.0%.

[0038] Potassium persulfate (CAS: 7727-21-1), purity greater than 99.5%.

[0039] Sodium dodecyl sulfate (CAS: 151-21-3), analytical grade.

[0040] n-Hexadecane (CAS: 544-76-3), purity greater than 98.0%.

[0041] Rhodamine B base (CAS: 509-34-2), chemical name 9-(2-carboxyphenyl)-3,6-bis(diethylamino)xanthine, is a pure hydrophobic red-light free base dehydrochlorinated, with a purity greater than 98.0%.

[0042] N,N'-bis(2,6-diisopropylphenyl)-3,4,9,10-perylenetetracarboxylic acid diimide (CAS: 82953-57-9) is a pure hydrophobic yellow-green to orange-yellow luminescent central dye with a measured emission peak in the yellow-green to orange-yellow band and a purity greater than 98.0%.

[0043] Pyrene (CAS: 129-00-0) is a pure hydrophobic polycyclic aromatic blue dye containing four fused benzene rings, with a purity greater than 98.0%.

[0044] Aqueous multifunctional carbodiimide crosslinking agent, commercially available.

[0045] Trimethylolpropane-tris(3-aziridinepropionate) (CAS: 52234-82-9), a multifunctional crosslinking primer with a purity greater than 99.0%.

[0046] Sodium polyacrylate (CAS: 9003-04-7) is a linear homopolymer with a carbon-carbon single bond main chain and sodium acrylate groups as repeating structural units. It has an average molecular weight of 3,000,000 to 5,000,000 and is available in powder form.

[0047] Sodium alginate (CAS: 9005-38-3), chemically pure.

[0048] Ethyl acetate (CAS: 141-78-6), chromatographic grade, purity greater than 99.9%.

[0049] Isopropanol (CAS: 67-63-0), chromatographic grade, purity greater than 99.9%.

[0050] Waterborne aliphatic polyurethane emulsion, anionic, with a solid content of 30%, and free of crosslinking agents.

[0051] Deionized water has a resistivity greater than 18.2 MΩ·cm.

[0052] Pure cotton scouring cloth, without fluorescent whitening agents or finishing agents, commercially available.

[0053] Polyester plain weave fabric, with both warp and weft yarns made of polyethylene terephthalate filament, without fluorescent whitening agents or finishing agents, is commercially available.

[0054] Polyester-cotton blend plain weave fabric, in which the mass ratio of polyester to cotton is 65:35, is commercially available.

[0055] In this invention, the units of measurement for all materials and solvents are uniformly referred to as parts by weight.

[0056] Preparation Example 1: This preparation example provides a method for preparing highly loaded red polystyrene fluorescent microspheres A with surface-rich carboxyl groups, including the following steps: 0.096 parts of rhodamine B base were dissolved in a mixture of 11.28 parts of styrene and 0.72 parts of acrylic acid monomers, followed by the addition of 0.24 parts of n-hexadecane. The mixture was sonicated for 5 minutes to obtain an oil phase. 0.5 parts of sodium dodecyl sulfate were added to 100 parts of deionized water and mechanically stirred for 10 minutes to obtain an aqueous phase.

[0057] The oil phase was added dropwise to the aqueous phase at a rate of 3 parts / minute, and homogenized at 12,000 rpm for 15 minutes using a high-shear emulsifier at 25°C to form a fine emulsion system. The fine emulsion was transferred to a four-necked flask equipped with a condenser, a mechanical stirrer, and a nitrogen gas delivery tube. Nitrogen gas was bubbled through the flask for 30 minutes to remove oxygen from the system. Under nitrogen protection and mechanical stirring at 400 rpm, the system was heated to 75°C. 0.12 parts of potassium persulfate were dissolved in 5 parts of deionized water, and the addition was completed within 45 minutes using a constant-pressure dropping funnel to control the dropping rate.

[0058] The reaction was continued at 75°C for 8 hours. After the reaction was completed, the mixture was cooled to 25°C and dialyzed in deionized water for 48 hours through a dialysis bag with a molecular weight cutoff of 8,000 to 14,000 to remove unreacted monomers, free emulsifiers, and unencapsulated surface free dyes. Finally, the solid content was adjusted to 15% by concentration treatment to obtain a stock solution A of highly loaded red polystyrene fluorescent microspheres with carboxyl groups on the surface.

[0059] Preparation Example 2: This preparation example provides a method for preparing highly loaded yellow-green to orange-yellow polystyrene fluorescent microspheres B with surface rich in carboxyl groups, including the following steps: 0.06 parts of N,N'-bis(2,6-diisopropylphenyl)-3,4,9,10-perylenetetracarboxylic acid diimide were dissolved in a mixture of 11.4 parts of styrene and 0.6 parts of acrylic acid monomers. Then, 0.12 parts of n-hexadecane were added, and the mixture was sonicated for 5 minutes to obtain the oil phase. 0.2 parts of sodium dodecyl sulfate were added to 100 parts of deionized water, and the mixture was mechanically stirred for 10 minutes to obtain the aqueous phase.

[0060] The oil phase was added dropwise to the aqueous phase at a rate of 2 parts / minute, and homogenized at 25°C using a high-shear emulsifier at 10,000 rpm for 20 minutes to form a fine emulsion system. The fine emulsion was transferred to a four-necked flask equipped with a condenser, a mechanical stirrer, and a nitrogen gas inlet tube. Nitrogen gas was bubbled through the flask for 30 minutes to remove oxygen from the system. Under nitrogen protection and mechanical stirring at 300 rpm, the system was heated to 70°C. 0.06 parts of potassium persulfate were dissolved in 5 parts of deionized water, and the addition was completed within 30 minutes using a constant-pressure dropping funnel to control the dropping rate.

[0061] The reaction was continued at 70°C for 10 hours. After the reaction was completed, the mixture was cooled to 25°C and dialyzed in deionized water for 48 hours through a dialysis bag with a molecular weight cutoff of 8,000 to 14,000 to remove unreacted monomers, free emulsifiers, and unencapsulated surface free dyes. Finally, the solid content was adjusted to 10% by concentration treatment to obtain the stock solution B of highly loaded yellow-green to orange-yellow polystyrene fluorescent microspheres with carboxyl groups on the surface.

[0062] Preparation Example 3: This preparation example provides a method for preparing highly loaded blue polystyrene fluorescent microspheres C with surface-rich carboxyl groups, including the following steps: 0.12 parts of pyrene were dissolved in a mixture of 11.16 parts of styrene and 0.84 parts of acrylic acid monomers, followed by the addition of 0.36 parts of n-hexadecane. The mixture was sonicated for 5 minutes to obtain an oil phase. 0.8 parts of sodium dodecyl sulfate were added to 100 parts of deionized water and mechanically stirred for 10 minutes to obtain an aqueous phase.

[0063] The oil phase was added dropwise to the aqueous phase at a rate of 4 parts / minute, and homogenized at 15,000 rpm for 10 minutes using a high-shear emulsifier at 25°C to form a fine emulsion system. The fine emulsion was transferred to a four-necked flask equipped with a condenser, a mechanical stirrer, and a nitrogen gas delivery tube. Nitrogen gas was bubbled through the flask for 30 minutes to remove oxygen from the system. Under nitrogen protection and mechanical stirring at 500 rpm, the system was heated to 80°C. 0.18 parts of potassium persulfate were dissolved in 5 parts of deionized water, and the addition was completed within 60 minutes using a constant-pressure dropping funnel to control the dropping rate.

[0064] The reaction was continued at 80°C for 6 hours. After the reaction was completed, the mixture was cooled to 25°C and dialyzed in deionized water for 48 hours through a dialysis bag with a molecular weight cutoff of 8,000 to 14,000 to remove unreacted monomers, free emulsifiers, and unencapsulated surface free dyes. Finally, the solid content was adjusted to 20% by concentration treatment to obtain the stock solution C of highly loaded blue polystyrene fluorescent microspheres with carboxyl groups on the surface.

[0065] Example 1: This embodiment provides a method for preparing anti-counterfeiting patterns on screen-printed fabrics based on fluorescent microspheres, including the following steps: S1. Use image processing software to design a monochrome or multicolor fluorescent screen printing partition pattern. Divide the pattern into a main anti-counterfeiting area and a homogeneous fluorescent noise calibration area. The main anti-counterfeiting area is designed as a dot matrix QR code containing multi-level encrypted text and its minimum line width is controlled at 0.15mm+. The homogeneous fluorescent noise calibration area is set as four square reference color blocks located at the four corners of the pattern. Set the decoding rule of red color block mapping to the number 1. S2. Add 3.5 parts of water-based multifunctional carbodiimide crosslinking agent and 0.3 parts of nonionic wetting agent to 96.5 parts of deionized water, and stir at 400 rpm for 15 minutes at 25°C using a magnetic stirrer to prepare the primer working solution. Apply the primer working solution to the surface of pure cotton scouring fabric using a two-roller two-dip two-roller process. Set the roller running pressure to 0.3 MPa to control the liquid application rate to 70%. Use the nonionic wetting agent to reduce the surface tension of the system, so that the working solution can achieve uniform wetting and spreading on the surface of pure cotton fibers and avoid local aggregation of crosslinking agent. Then, lay the pure cotton scouring fabric flat and send it into a hot air setting machine, and dry it at 90°C for 3 minutes to complete the primer crosslinking pretreatment of the textile substrate. S3. First, add 58 parts of deionized water to the preparation container, turn on the mechanical stirrer and set the speed to 300 rpm. While stirring, add 2 parts of powdered sodium polyacrylate in 5 portions within 5 minutes, and continue stirring for 120 minutes until it is completely swollen. Then add 40 parts of high-load red polystyrene fluorescent microsphere stock solution A, and adjust the speed of the mechanical stirrer to 600 rpm at 25°C and continue stirring for 30 minutes. During this process, no film-forming binder is added to prepare a fluorescent color paste without film-forming binder. S4. Using a 300-mesh screen with a screen tension set to 20 N / cm, a polyurethane squeegee is used to print fluorescent pigments without film-forming binders onto the surface of a pure cotton scouring cloth that has undergone a base coating crosslinking pretreatment, according to the color separation artwork. After printing, the fabric is placed in a continuous baking oven and baked at 135°C for 4 minutes. The heat energy promotes the coupling or crosslinking anchoring reaction of the free carboxyl groups on the surface of the microspheres under the action of the active components of the base coating, thus obtaining a screen-printed anti-counterfeiting pattern based on fluorescent microspheres. S5. Add 30 parts of ethyl acetate and 70 parts of isopropanol to a light-proof glass bottle, and mix them at 200 rpm for 5 minutes at 25°C using a shaker to prepare a security verification solution for subsequent transient limited swelling response anti-counterfeiting verification.

[0066] Example 2: This embodiment provides a method for preparing anti-counterfeiting patterns on screen-printed fabrics based on fluorescent microspheres, including the following steps: S1. Use image processing software to design monochrome or multicolor fluorescent screen printing partitioned artwork, divide the artwork into a main anti-counterfeiting area and a homologous fluorescent noise calibration area. The main anti-counterfeiting area is designed as an anti-counterfeiting mark composed of micro letters and geometric shapes, and its minimum line width is controlled at 0.2mm. The homologous fluorescent noise calibration area is set as 3 circular reference color blocks located at the lower edge of the pattern, and the decoding rule of mapping yellow-green to orange-yellow color blocks to the letter A is set. S2. Add 2 parts of trimethylolpropane-tris(3-aziridinepropionate) and 0.2 parts of nonionic wetting agent to 98 parts of deionized water, and stir at 300 rpm for 20 minutes at 25°C using a magnetic stirrer to prepare the primer working solution. Apply the primer working solution to the surface of polyester plain weave fabric using a two-roller two-dip two-ply process. Set the roller running pressure to 0.25 MPa to control the liquid application rate to 60%. The nonionic wetting agent overcomes the strong hydrophobicity of the polyester surface, allowing the working solution to evenly wet the fabric surface and penetrate deeply into the yarn gaps. Then, lay the polyester plain weave fabric flat and put it into a hot air setting machine, and dry it at 80°C for 2 minutes to allow the crosslinking agent to form a uniform physical adhesion layer on the surface and gaps of the chemically inert polyester fibers, completing the primer crosslinking pretreatment of the textile substrate. S3. First, add 69 parts of deionized water to the preparation container, turn on the mechanical stirrer and set the speed to 200 rpm. While stirring, add 1 part of sodium alginate within 3 minutes and continue stirring for 60 minutes until it gelatinizes. Then add 30 parts of high-load yellow-green to orange-yellow polystyrene fluorescent microsphere stock solution B, adjust the mechanical stirrer speed to 500 rpm at 25°C and continue stirring for 30 minutes to prepare a fluorescent color paste without film-forming binder. S4. Using a 200-mesh screen with a screen tension set to 18 N / cm, a polyurethane squeegee is used to print fluorescent pigments without film-forming binders onto the surface of a polyester plain weave fabric that has undergone a base coating crosslinking pretreatment, according to the color separation artwork. After printing, the fabric is placed in a continuous baking oven and baked at 120°C for 3 minutes to obtain a screen-printed anti-counterfeiting pattern based on fluorescent microspheres. S5. Add 20 parts of ethyl acetate and 80 parts of isopropanol to a light-proof glass bottle, and mix them at 150 rpm for 8 minutes at 25°C using a shaker to prepare a security verification solution for subsequent transient limited swelling response anti-counterfeiting verification.

[0067] Example 3: This embodiment provides a method for preparing anti-counterfeiting patterns on screen-printed fabrics based on fluorescent microspheres, including the following steps: S1. Use image processing software to design monochrome or multicolor fluorescent screen printing partitioned artwork, divide the artwork into main anti-counterfeiting area and homogeneous fluorescent background noise calibration area. The main anti-counterfeiting area is designed as a high-frequency invisible watermark and camouflage interwoven pattern with a minimum line width of 0.1mm. The homogeneous fluorescent background noise calibration area is set as 5 rectangular reference color blocks around the pattern, and the blue color block is mapped to the decoding rule of the symbol #. S2. Add 5 parts of water-based multifunctional carbodiimide crosslinking agent and 0.5 parts of nonionic wetting agent to 95 parts of deionized water, and stir at 600 rpm for 10 minutes at 25°C using a magnetic stirrer to prepare the primer working solution. Apply the primer working solution to the surface of the polyester-cotton blended plain weave fabric using a two-roller padding process. Set the padding pressure to 0.35 MPa to control the padding rate to 80%. Use the nonionic wetting agent to balance the surface energy difference between the polyester and cotton components to ensure that the working solution penetrates uniformly and indiscriminately in the blended fabric network. Then, lay the polyester-cotton blended plain weave fabric flat and put it into a hot air setting machine, and dry it at 100°C for 5 minutes to make the crosslinking agent evenly distributed and attached to the blended fiber skeleton, thus completing the primer crosslinking pretreatment of the textile substrate. S3. First, add 47 parts of deionized water to the preparation container, turn on the mechanical stirrer and set the speed to 400 rpm. While stirring, add 3 parts of powdered sodium polyacrylate in 3 portions over 10 minutes, and continue stirring for 180 minutes until it is completely swollen. Then add 50 parts of high-load blue polystyrene fluorescent microsphere stock solution C, and adjust the speed of the mechanical stirrer to 800 rpm at 25°C and continue stirring for 30 minutes to prepare a fluorescent color paste without film-forming binder. S4. Using a 400-mesh screen with a screen tension set to 22 N / cm, a polyurethane squeegee is used to print fluorescent pigments without film-forming binders onto the surface of a polyester-cotton blend plain weave fabric that has undergone a base coating crosslinking pretreatment, according to the color separation artwork. After printing, the fabric is placed in a continuous baking oven and baked at 150°C for 5 minutes to obtain a screen-printed anti-counterfeiting pattern based on fluorescent microspheres. S5. Add 40 parts of ethyl acetate and 60 parts of isopropanol to a light-proof glass bottle, and mix them at 250 rpm for 4 minutes using a shaker at 25°C to prepare a security verification solution for subsequent transient limited swelling response anti-counterfeiting verification.

[0068] Comparative Example 1: Compared with Example 1, the difference is that the pretreatment operation of the base coating crosslinking in step S2 is omitted, and in step S4, the fluorescent pigment without film-forming adhesive is directly overprinted on the surface of untreated pure cotton scouring cloth. All other aspects are the same.

[0069] Comparative Example 2: Compared with Example 1, the difference is that the primer crosslinking pretreatment operation in step S2 is omitted, and in step S3, the amount of deionized water is adjusted from 58 parts to 43 parts, and 15 parts of waterborne aliphatic polyurethane emulsion is added as a film-forming binder to prepare a conventional fluorescent color paste. All other aspects are the same.

[0070] Comparative Example 3: Compared with Example 1, the difference is that the color separation pattern designed using image processing software in step S1 only includes the main anti-counterfeiting area, and does not set the homogeneous fluorescence background noise calibration area and its mapping decoding rules, while the rest are the same.

[0071] Comparative Example 4: Compared with Example 1, the difference is that the amount of rhodamine B base in the preparation method (i.e., Preparation Example 1) of the red polystyrene fluorescent microsphere stock solution used in step S3 was significantly reduced from 0.096 parts to 0.005 parts, so that the dye molecules did not reach the critical state of aggregation and quenching inside the microspheres. All other aspects are the same.

[0072] Comparative Example 5: Compared with Example 1, the difference is that in step S3, instead of using the high-load red polystyrene fluorescent microsphere stock solution, 0.05 parts of unencapsulated free rhodamine B base dye were used, and 15 parts of aqueous aliphatic polyurethane emulsion were added as a film-forming binder. It was mixed with 2 parts of sodium polyacrylate and 82.95 parts of deionized water to prepare a conventional fluorescent color paste. All other aspects were the same.

[0073] Test Example 1: Cut out anti-counterfeiting pattern samples of screen-printed fabrics based on fluorescent microspheres prepared in Examples 1 to 3, with a size of 2cm × 2cm, and fix them flat on a quartz glass slide, with the test area covering the main anti-counterfeiting area.

[0074] The slide was placed in the solid sample holder of the fluorescence spectrophotometer. The excitation wavelength was set according to the absorption characteristics of the fluorescent microspheres corresponding to each embodiment. The absolute intensity of the steady-state fluorescence emission peak of the sample in the initial dry state was continuously scanned and extracted.

[0075] While maintaining the test geometry of the slide in the sample chamber and the photomultiplier tube parameters of the instrument, 50 μL of the corresponding security verification solution was dropped onto the center of the main anti-counterfeiting area of ​​the sample using a microsyringe. The emission spectrum was rapidly acquired within 3 seconds after the addition, and the captured peak fluorescence emission intensity was recorded as transient wet state data.

[0076] The sample with the added verification solution, along with the slide, was transferred to a fume hood and left to stand naturally at 25°C for 15 minutes. After the verification solution had completely evaporated and the substrate had dried, it was placed back into the test chamber to measure the absolute intensity of the fluorescence emission peak at the same location. The above test was performed in parallel for each embodiment, and the average value was calculated.

[0077] Table 1: Fluorescence intensity test data of the swelling response of the patterned samples from Examples 1 to 3

[0078] According to Table 1 and Figure 1 According to the data, the absolute fluorescence emission intensity of Examples 1 to 3 in the initial dry state was all below 600 RFU. The fluorescence intensity of the pattern on the fabric surface was relatively weak under conventional ultraviolet excitation. The high dye loading set in the microsphere synthesis stage caused the dye molecules to aggregate highly at high concentrations. The close spatial distance produced an aggregation quenching effect, reducing the steady-state fluorescence intensity of the material.

[0079] After the safety verification solution was added, the testing system recorded a significant increase in the fluorescence emission intensity of each sample within 3 seconds. The transient fluorescence surge in Example 1 reached 9.1 times. The good solvent component in the verification solution penetrated into the interior of the microspheres, and the polystyrene matrix cross-linked and anchored on the fibers underwent restricted three-dimensional physical swelling. The stretching of the polymer chain segments increased the physical spacing between the internal dye molecules, releasing the aggregation and quenching state of the system. After the verification solution was basically evaporated at 25°C, the polymer network that lost the solvent effect gradually contracted and returned to a higher glassy rigidity state. The fluorescence data in the dried state after evaporation then dropped back to a level similar to the initial data.

[0080] The difference between the two sets of dry state data in the test is due to the conformational hysteresis when the macromolecular chains rewind. The overall numerical change reflects the basic reversible physical effect of the optical response mechanism of restricted swelling and aggregation quenching on the textile carrier. The transient change in fluorescence intensity under specific solvent excitation constitutes the physical basis for this scheme to identify counterfeit products.

[0081] Test Example 2: Samples of anti-counterfeiting patterns on screen-printed fabrics based on fluorescent microspheres prepared in Examples 1 to 3 and Comparative Example 3 were cut and laid flat and fixed on a standard white cotton backing plate that had been treated with fluorescent whitening agent. In a dark room, a fixed ultraviolet light source with a center wavelength of 365nm was turned on to excite the bottom backing plate to generate a blue fluorescent background noise.

[0082] A barcode scanning terminal device equipped with a CMOS image sensor and a spectral feature extraction algorithm module was set up. The lens optical axis was vertically aligned with the center anti-counterfeiting area of ​​the test sample. The working distance from the terminal lens to the fabric surface was set to 15cm, and the visible light illuminance in the test chamber was controlled below 10Lux.

[0083] The scanning terminal is activated to continuously read the anti-counterfeiting area on the surface of the fabric sample. The timeout threshold for a single image capture and calculation is set to 1000ms. Each test sample is continuously executed 50 independent scanning trigger actions.

[0084] Extract the total number of scan triggers, the number of times the mapped ciphertext was successfully output, and the time consumed for each successful decoding from the device's background records. Calculate the decoding success rate and average decoding time for each group of samples.

[0085] Table 2: Test data of scanning decoding performance under strong background fluorescence interference environment

[0086] Combined with Table 2 and Figure 2 It can be seen that the decoding success rate of the samples in Examples 1 to 3 remained between 94.0% and 98.0%, and the average decoding time was between 142.6ms and 161.8ms. The decoding success rate of Comparative Example 3 under the same background light source decreased to 16.0%, and the average time for a single successful extraction of ciphertext was extended to 895.4ms, which is close to the timeout threshold boundary set by the system.

[0087] Fluorescent whitening agents commonly used in daily textile finishing processes produce a broadband blue emission spectrum under ultraviolet excitation. This optical noise causes channel crosstalk between the color channel of the image sensor and the fluorescent signal of the printed microspheres, and overlaps with some emission bands. Consequently, the overall color coordinates acquired by the image sensor are shifted and distorted. In the embodiment design, the homogeneous fluorescent noise calibration area and the main anti-counterfeiting ciphertext are printed synchronously with the same batch of fluorescent pigments without film-forming adhesives. Both are subjected to consistent background emission spectrum interference on the substrate surface. When the reading terminal captures the image, it prioritizes locating the calibration color block at the edge of the pattern. By calculating the difference between its preset standard color information and the actual received spectrum, a reverse compensation matrix for the current fabric environment is generated.

[0088] The system executes the compensation matrix during the digital reconstruction of the dot matrix image of the main anti-counterfeiting area, strips off the emission signal generated by the fluorescent whitening agent of the base fabric, and the scanning chip performs a mapping operation based on the restored color coordinates. Compared with the design of Example 3 which lacks this reference color block, the scanning terminal has difficulty in stably separating the effective spectral signal from the background noise. The drift of the color coordinates causes the dot matrix image to be interpreted incorrectly. The scanning terminal triggers the internal retry and focus verification mechanism, resulting in the extension of the recognition cycle and the final decoding failure. By setting a homogeneous environment reference and spectral compensation algorithm on the surface of the fabric carrier with background luminescent interference, the stable extraction and decoding of optical anti-counterfeiting marks can be achieved.

[0089] Test Example 3: Printed fabric samples prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 5 were cut into test specimens of corresponding sizes according to the physical performance test standards. All specimens were laid flat and placed in a constant temperature and humidity standard atmospheric environment with a temperature set at 20°C and a relative humidity set at 65% for 24 hours to adjust the humidity.

[0090] A rubbing fastness tester was used. A standard cotton rubbing cloth with a moisture content of 100% was fixed on the rubbing head of the tester. A vertical downward pressure load of 9N was applied to the surface of the sample. Ten reciprocating linear rubbing actions were performed continuously in the central area covering the printed pattern. The rubbing cloth was then removed and moved into a standard light source box. The wet rubbing fastness grade of each sample was evaluated by comparison with a gray scale.

[0091] Using a fully automatic fabric air permeability meter, place the corresponding sample flat on the instrument's test platform and close the clamp. Set the airflow penetration test area to 20 square centimeters, adjust the instrument's fan speed to stabilize the test pressure drop on both sides of the sample at 100 Pa, and read and record the absolute value of the air permeability when the airflow passes through the fabric stably and vertically.

[0092] Using a fabric stiffness tester, the cut warp and weft samples are placed on a horizontal test platform. The instrument is started and the sample is pushed out longitudinally at a slow and constant speed. The sliding length of the sample when the front end droops due to its own weight and is tangent to the inclined plane at an angle of 41.5 degrees is recorded. The bending stiffness value of each sample is calculated and output by combining the pre-measured fabric areal density data.

[0093] Table 3: Test data of physical and mechanical properties of printed fabric samples

[0094] Combined with Table 3 and Figure 3The data shows that, in Comparative Example 1, due to the lack of primer cross-linking pretreatment and the absence of film-forming adhesive for fixation, the fluorescent microspheres detached from chemical bonding and adhered to the cotton fibers solely through physical adsorption, resulting in a drop in wet rubbing color fastness to grade 1.5. In Comparative Examples 2 and 5, the color fastness improved to grade 3.5 or higher after the introduction of polyurethane emulsion. However, the continuous phase film formed during drying inevitably blocked the fiber gaps, causing the air permeability to drop to around 300 mm / s, while the flexural stiffness increased exponentially to over 5.60 cN·cm, exhibiting significant air permeability degradation and structural hardening.

[0095] Example 1 achieved a wet rubbing color fastness of 4.5, and its air permeability (842.7 mm / s) and bending stiffness (1.86 cN·cm) were highly similar to those of the untreated Comparative Example 1. After applying a base coat containing an aqueous multifunctional carbodiimide, the high-temperature baking heat at 135°C drove the free carboxyl groups on the surface of the microspheres to undergo a coupling and anchoring reaction with the hydroxyl groups on the fiber surface or the active sites of the base coat under the cross-linking effect of the multifunctional carbodiimide. The microsphere particles were anchored to the fiber skeleton through coupling or cross-linking. The resulting coupling anchoring points improved the peel resistance of the microspheres under wet rubbing conditions with a 9N load. Spatial chemical cross-linking replaced the traditional polymer physical film-forming process of printing. Under the condition of eliminating the resin network coverage, the microporous structure and airflow channels of the fabric remained in their original state, taking into account both the color fastness of the print and the original physical softness of the substrate.

[0096] Test Example 4: Cut the printed fabric samples prepared in Example 1, Comparative Example 2 and Comparative Example 5, and fix them flat on the stage of the two-dimensional image measuring instrument, keeping the warp and weft yarns of the fabric in a naturally stretched state.

[0097] Turn on the ring LED cold light source illumination system of the measuring instrument, set the magnification of the microscope objective to 50x, and align it with the edge lines of the dot matrix QR code in the main anti-counterfeiting area of ​​the sample, which has a theoretical line width of 0.15mm.

[0098] Twenty measurement sections were selected along the line extension direction. The actual printed line width was measured using the edge automatic capture function of the image processing software, and the specific width value of each section was extracted.

[0099] The actual average line width and line width expansion rate of each group of samples were calculated based on the theoretical design size of 0.15mm, and the coefficient of variation of the extracted data was calculated as a quantitative index to characterize the edge roughness of the printed lines.

[0100] Table 4: Test data on the fineness and edge quality of printed patterns

[0101] Combined with Table 4 and Figure 4According to the data, the actual average line widths of the samples in Comparative Example 2 and Comparative Example 5 expanded to 0.236 mm and 0.249 mm, respectively, with corresponding line width expansion rates of 57.33% and 66.00%. In conventional printing processes, the water-based aliphatic polyurethane emulsion contained in the pigment system has specific rheological and fiber wetting characteristics. Under the magnified field of view of the image measuring instrument, it was observed that the resin paste printed onto the fabric surface underwent significant liquid penetration along the capillary pores formed by the interwoven cotton fibers during room temperature standing and the initial stage of baking. Fluorescent microspheres or free dyes migrated to the outside of the pattern boundary along with the flow of the polymer resin phase, causing the micro QR code line size to thicken and the pattern edge contour to show irregular serrated diffusion, resulting in a significant increase in its edge roughness variation coefficient to over 14.85%.

[0102] The actual average linewidth of the sample in Example 1 was measured to be 0.154 mm. The linewidth expansion rate and the coefficient of variation of edge roughness were controlled at low levels of 2.67% and 3.12%, respectively. A fluorescent pigment without film-forming binder was used to eliminate the capillary rheological drag phenomenon caused by the long polymer chain. After the microsphere particles were transferred to the fabric surface through the mesh, the free carboxyl groups on their surface under the action of baking heat energy at 135°C, with the participation of the pre-prepared active component of the base coating, underwent in-situ coupling or cross-linking anchoring reaction. The rapid generation of covalent bonds anchored the microspheres to the initial printing point. The intervention of cross-linking at the solid phase interface blocked the physical path of capillary diffusion of pigment particles along the yarn texture.

[0103] By using a spatially distributed chemical reaction system to replace the traditional resin coating film system, the fluid diffusion limit is controlled while maintaining the dye adhesion strength. This solves the problem of water-based slurry bleeding and smudging on porous surfaces and meets the dimensional accuracy control requirements of high-density anti-counterfeiting dot matrix images on rough textile substrates.

[0104] Test Example 5: Separately cut printed fabric samples prepared in Example 1, Comparative Example 4 and Comparative Example 5, with a size of 2cm×2cm, and use a special clamp to lay them flat and fix them on the surface of a quartz glass slide, so that the light spot at the center of the test is aligned with the main anti-counterfeiting area of ​​the sample.

[0105] The slide containing the fabric sample was pushed into the test chamber of the fluorescence spectrophotometer. The incident excitation wavelength was set according to the absorption characteristics of Rhodamine B base, and the steady-state spectrum of the sample was scanned to extract the absolute intensity value of the fluorescence emission peak in the initial dry state.

[0106] Keeping the slide in the absolute position in the test optical path unchanged, 50 μL of safety verification solution prepared by mixing ethyl acetate and isopropanol is added to the center of the sample test area at one time using a micro-syringe. Within the 3-second time window of solvent immersion in the fabric, the high-speed continuous acquisition mode of the instrument is activated, and the highest peak value in the captured emission spectrum is recorded as the transient wet state peak fluorescence intensity.

[0107] The sample that had been soaked in solvent was placed in a ventilated environment at 25°C and left to stand for 20 minutes until the solvent evaporated. The fabric sample that had been restored to a dry state was then moved back to its original position in the test chamber. The absolute intensity of the fluorescence emission peak at this time was measured and recorded. The fluorescence surge factor of the corresponding sample was calculated by the ratio of the peak intensity to the initial steady-state intensity.

[0108] Table 5: Comparative Test Data on Anti-counterfeiting of Dynamic Response Characteristics

[0109] Combined with Table 5 and Figure 5 The data shows that in Comparative Example 4, the reduction in the dye loading of the microspheres increased the intermolecular distance within the system. Rhodamine B base molecules did not reach the critical state of aggregation quenching within the microsphere polymer matrix. The sample was recorded to have a fluorescence emission floor of 3512.7 RFU in the initial dry state. The addition of the verification solution caused the three-dimensional physical expansion of the cross-linked microspheres, expanding the internal space. The system, which originally lacked quenching limitations, did not show a jump in fluorescence intensity, but only a decrease under the solvent wetting and dilution effect. The fluorescence surge factor was measured to be only 0.98. In Comparative Example 5, a formulation system using traditional waterborne polyurethane film to embed free dyes was used. After the polar organic solvent in the verification solution came into contact with the fabric surface, it penetrated into the resin layer and caused the continuous resin phase to swell, plasticize, and locally destroy its structure. The free dye molecules detached from the attached system and migrated along the fabric fiber texture, causing a direct decrease in the luminescent density in the test area. The transient fluorescence intensity of this sample decayed to 1145.8 RFU, and the secondary measurement value after solvent evaporation further decreased to 623.1 RFU.

[0110] In Example 1, the high dye doping concentration set during the microsphere synthesis stage shortened the physical distance between the luminescent organisms. The tight molecular stacking suppressed the initial steady-state fluorescence to a low value range of 425.6 RFU. The addition of a verification mixture containing ethyl acetate and isopropanol excited the physical swelling of the cross-linked polystyrene matrix. Under the restricted state, the extension of the polymer chain segments pulled the dye monomers to disperse, breaking the critical distance limitation of aggregation quenching. The test system recorded an optical signal amplification of 9.10 times.

[0111] The subsequent solvent evaporation stage is accompanied by the shrinkage of the polymer skeleton, which restores the high-density spatial stacking and reproduces the initial low fluorescence characteristics. Conventional printing processes and low-concentration dye components without polymer modification show signal decay or remain normal when in contact with specific chemical solvents. The limited deformation of the material at the microscopic spatial scale drives the intermolecular spacing of fluorescent molecules to achieve cross-threshold regulation. The macroscopically reversible optical response transition reflects the chemical composition characteristics inside the system, providing a physical basis for identifying the anti-counterfeiting properties of printed patterns.

[0112] Test Example 6: The printed fabric samples prepared in Example 1, Comparative Example 2 and Comparative Example 5 were cut into 50mm×150mm test specimens according to the AATCC61 standard and placed into a closed high-temperature resistant water washing tank equipped with stainless steel balls.

[0113] Pour the prepared 0.23% AATCC standard reference detergent solution into the washing tank, adjust the constant temperature water bath system to stabilize the washing liquid temperature at 60℃, start the water wash color fastness tester, set the speed to 40r / min for mechanical tumbling washing, each 45 minutes of operation is counted as one industrial water washing cycle, and 50 cycles are executed continuously.

[0114] After completing the 10th, 30th and 50th washing cycles, each group of samples was taken out, the residual detergent on the surface was rinsed with deionized water, and dried in a 60°C forced-air drying oven to constant weight. The absolute fluorescence intensity of the central anti-counterfeiting area of ​​each sample at the corresponding washing node was extracted using a fluorescence spectrophotometer. The fluorescence retention rate was calculated by combining the fluorescence data of the initial drying state of the same batch of samples before washing.

[0115] The samples that have completed each stage of washing and drying were laid flat on the test bench in the darkroom. A fixed barcode scanning terminal equipped with a CMOS image sensor was used to continuously read the anti-counterfeiting area of ​​the fabric 50 times. The actual decoding success rate of each sample at different washing and aging stages was recorded and statistically analyzed.

[0116] Table 6: Test data on optical stability and decoding performance under continuous industrial washing conditions

[0117] Combined with Table 6 and Figure 6The data shows that Comparative Example 5, which uses a mixture of waterborne polyurethane emulsion and free Rhodamine B alkali dye, experienced a fluorescence retention rate of 59.80% after 10 standard water washes, and a decoding success rate of the barcode terminal dropped to 0% after 50 washes. The surfactants in the washing solution and the weakly alkaline water environment caused the resin film to swell and undergo local hydrolysis. The free dye was eroded and detached under the mechanical tumbling and water shearing in the washing tank. Comparative Example 2, which embedded the dye inside the microspheres, initially showed higher wash resistance than Comparative Example 5. However, there was a difference in rigidity between its polyurethane resin continuous phase film and the flexible cotton fiber. With the accumulation of washing cycles, the resin film developed micro-cracks under thermodynamic impact, and the microspheres, along with the broken resin flakes, were completely detached from the substrate. After 50 washes, the decoding success rate dropped to 24.0%.

[0118] After 50 washing cycles, the fluorescence retention rate of the sample in Example 1 remained stable at 84.13%, and the decoding success rate remained at 92.0%. In a system without the participation of polymer film-forming resin, the free carboxyl groups carried on the microsphere shell underwent a coupling and anchoring reaction with the active sites on the fiber surface or the base coating at 135°C under the cross-linking effect of multifunctional carbodiimide. The resulting coupling or cross-linking anchoring points fixed the microsphere particles on the cotton cellulose skeleton or the base coating active layer. The high bond energy resisted the elution and peeling of surfactants and the degradation effect of a 60°C high-temperature water bath. The independent chemical anchoring morphology of the particles did not restrict the deformation of the original interlacing structure of the yarn, preserved the physical buffering ability of the flexible substrate against tumbling impact, dispersed the mechanical tearing and fluid shear stress during the washing process, controlled the information loss of the anti-counterfeiting pattern caused by wear, and maintained the optical feature readability of the fabric after multiple washing cycles.

[0119] Test Example 7: The printed fabric samples prepared in Example 1 and Comparative Example 5 were cut into 45mm×90mm specimens according to the ISO105-B02 test standard for color fastness to artificial light. Each specimen and the blue wool standard sample card were clamped in parallel on the specimen rack of the sunlight and weathering color fastness tester.

[0120] Turn on the xenon arc lamp light source of the tester, set the blackboard temperature to 65℃, adjust the relative humidity of the chamber to 40%, and control the spectral irradiance to be constant at 1.10W / (m²) at a wavelength of 420nm. 2 (nm), setting the instrument drum to rotate continuously at a speed of 1 rpm.

[0121] After 24 hours, 72 hours, and 168 hours of continuous light irradiation, the testing procedure was paused and the corresponding samples were removed. The light-aged samples were then moved to a dark room and laid flat to stand for 2 hours.

[0122] Steady-state spectral scanning of the samples before and after treatment at various time points was performed using a fluorescence spectrophotometer. 50 μL of safety verification solution was added to the center of the test area to trigger the fluorescence emission response. The absolute intensity of the peak fluorescence under transient wet conditions was extracted. Using the excitation peak value under the initial unaged state as a benchmark, the fluorescence intensity retention rate of each sample under different light exposure cycles was calculated, and the color fading state of the pattern was recorded.

[0123] Table 7: UV aging test data under continuous high-intensity xenon lamp irradiation

[0124] Combined with Table 7 and Figure 7 , Figure 8 The data shows that in Comparative Example 5, a direct mixture of waterborne polyurethane and free Rhodamine B base dye was used. When the dye molecules were exposed to external light and air, they underwent irreversible photo-oxidative degradation with the participation of free oxygen after absorbing high-energy ultraviolet photons. After 24 hours of continuous xenon arc lamp irradiation, the fluorescence retention rate of the system dropped sharply to 52.49%, and the printed pattern showed a large area of ​​whitening. With the accumulation of light exposure time, the conjugated chromophore network in the dye molecule structure broke down, and the excitation intensity decayed to 3.16% of the initial level after 168 hours, and the characteristic optical signal basically dissipated.

[0125] In Example 1, after 168 hours of high-intensity xenon arc radiation, the fluorescence intensity retention rate was measured to be 83.11%, and the surface of the anti-counterfeiting pattern on the sample only showed slight yellowing. This improvement in optical stability is based on the physical barrier mechanism of the cross-linked polystyrene microsphere shell. The relatively dense polymer matrix formed by emulsion polymerization or microemulsion polymerization reduces the mass transfer rate of oxygen and moisture in the external environment penetrating into the microsphere, stripping away the material basis required for photo-oxidative degradation reaction. The benzene ring side groups arranged in the long chain of polystyrene have the effect of absorbing and dissipating some short-wave ultraviolet light. When some high-energy photons emitted by the external xenon lamp come into contact with the surface of the microsphere, they can be absorbed by the benzene ring π electron system and dissipated through non-radiative transitions and other pathways.

[0126] The mass transfer barrier of this dense shell, combined with the energy dissipation of the benzene ring structure, significantly reduces the intensity of light radiation penetrating to the core region of the microsphere. This protects the Rhodamine B base molecules embedded in the matrix from the massive attacks of high-energy ultraviolet rays and free active oxygen molecules, maintaining the structural integrity of the luminescent molecular skeleton and ensuring the reliable detection of anti-counterfeiting features of the fabric under long-term light aging conditions.

[0127] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A screen-printed anti-counterfeiting pattern for fabrics based on fluorescent microspheres, characterized in that, It includes a textile substrate, a primer pretreatment layer bonded to the surface of the textile substrate, and an anti-counterfeiting printing layer bonded to the surface of the primer pretreatment layer; The anti-counterfeiting printing layer is printed and baked with fluorescent pigment without film-forming adhesive, and the anti-counterfeiting printing layer contains high-load polystyrene fluorescent microspheres, which are cross-linked and anchored to the base coating pretreatment layer or textile substrate through chemical bonds. The fluorescent color paste without film-forming binder comprises the following components in parts by weight: 47 to 69 parts of deionized water; Thickener 1 to 3 parts; 30 to 50 parts of stock solution of highly loaded polystyrene fluorescent microspheres with surface rich in carboxyl groups; Under normal dry conditions, the fluorescent dye embedded inside the microspheres is in a high-concentration aggregation and quenching state because the intermolecular distance is less than the quenching critical distance. The anti-counterfeiting optical signal is significantly suppressed, making the pattern appear as a low-fluorescence concealed state on a macroscopic scale. When wetted by the safety verification solution, the shell of the high-density polystyrene microspheres undergoes transient confined swelling, breaking the aggregation state of the dye molecules and exciting the release of the corresponding characteristic fluorescence signal.

2. The anti-counterfeiting pattern for screen-printed fabric based on fluorescent microspheres according to claim 1, characterized in that, The surface-rich carboxyl-enriched, highly loaded polystyrene fluorescent microsphere stock solution is polymerized from raw materials comprising the following parts by weight: 105 parts of deionized water; Styrene: 11.16 to 11.4 parts; Acrylic acid 0.6 to 0.84 parts; 0.06 to 0.12 parts of fluorescent dye; 0.12 to 0.36 parts of n-hexadecane; Sodium dodecyl sulfate, 0.2 to 0.8 parts; Potassium persulfate 0.06 to 0.18 parts.

3. The anti-counterfeiting pattern for screen-printed fabric based on fluorescent microspheres according to claim 2, characterized in that, The textile substrate is one of pure cotton scourted plain weave, polyester plain weave, or polyester-cotton blend plain weave. The active crosslinking groups contained in the primer pretreatment layer are one of the following: an aqueous multifunctional carbodiimide crosslinking agent or trimethylolpropane-tris(3-aziridinepropionate); The thickener in the fluorescent color paste without film-forming binder is either powdered sodium polyacrylate or sodium alginate. The fluorescent dye is one of rhodamine B base, N,N'-bis(2,6-diisopropylphenyl)-3,4,9,10-perylenetetracarboxylic acid diimide, or pyrene.

4. The anti-counterfeiting pattern for screen-printed fabric based on fluorescent microspheres according to claim 1, characterized in that, The anti-counterfeiting pattern, in conjunction with the security verification liquid, performs anti-counterfeiting verification. The security verification liquid is separate from the patterned product and contains the following components in parts by weight: 20 to 40 parts of ethyl acetate 60 to 80 parts of isopropanol.

5. The anti-counterfeiting pattern for screen-printed fabric based on fluorescent microspheres according to claim 1, characterized in that, The anti-counterfeiting pattern includes a main anti-counterfeiting area and a homogeneous fluorescence noise calibration area. The minimum line width of the main anti-counterfeiting area is controlled between 0.1 and 0.2 mm. The homogeneous fluorescence noise calibration area is provided with a reference color block for mapping the decoding rules of numbers, letters or symbols.

6. A method for preparing anti-counterfeiting patterns on screen-printed fabrics based on fluorescent microspheres according to any one of claims 1-5, characterized in that, Includes the following steps: S1. Use image processing software to design monochrome or multicolor fluorescent screen printing partition artwork; S2. Apply the primer working liquid to the surface of the textile substrate, and then send it into a hot air setting machine to dry, thus completing the primer crosslinking pretreatment of the textile substrate. S3. Add a thickener to water and stir until it is completely swollen or gelatinized. Then add the high-load polystyrene fluorescent microsphere stock solution with rich carboxyl groups on the surface and continue stirring without adding a film-forming binder to prepare a fluorescent paste without a film-forming binder. S4. The fluorescent pigment without film-forming adhesive is overprinted onto the surface of a textile substrate that has undergone a pre-treatment of cross-linking under a base coating according to the color separation pattern. After printing, the substrate is baked to use heat energy to promote the coupling or cross-linking anchoring reaction of free carboxyl groups on the surface of the microspheres under the action of the active components of the base coating, thereby obtaining a screen-printed anti-counterfeiting pattern for the fabric based on fluorescent microspheres.

7. The preparation method according to claim 6, characterized in that, In step S3, the stock solution of the highly loaded polystyrene fluorescent microspheres with rich carboxyl groups on the surface is prepared in advance as follows: The fluorescent dye was dissolved in a mixture of styrene and acrylic acid monomers, and the oil phase was prepared by adding n-hexadecane and sonicating. The aqueous phase was prepared by adding sodium dodecyl sulfate to 100 parts of deionized water and stirring. The oil phase is added dropwise to the aqueous phase and homogenized using a high-shear emulsifier to form a fine emulsion system. Under nitrogen protection and mechanical stirring, the system was heated to 70 to 80°C, and potassium persulfate solution dissolved in 5 parts of deionized water was added dropwise. The reaction temperature was maintained and the reaction continued for 6 to 10 hours. After the reaction is completed and cooled, unreacted monomers and free dyes are removed by dialysis, and the solid content is concentrated to 10% to 20%.

8. The preparation method according to claim 6, characterized in that, In step S2, the primer working solution is prepared from 2 to 5 parts by weight of an aqueous multifunctional carbodiimide crosslinking agent or trimethylolpropane-tris(3-aziridinium propionate) and 95 to 98 parts by weight of deionized water. The application method adopts a two-roll rolling mill with two dips and two rolls. The rolling mill operating pressure is controlled at 0.25 to 0.35 MPa, and the rolling liquid rate is 60% to 80%. The drying temperature of the hot air setting machine is 80 to 100℃, and the time is 2 to 5 minutes.

9. The preparation method according to claim 6, characterized in that, The specific implementation method of step S3 is as follows: first add deionized water, turn on the mechanical stirrer and set the speed to 200 to 400 rpm, add the thickener in batches or continuously within 3 to 10 minutes, continue stirring for 60 to 180 minutes, then add the high-load polystyrene fluorescent microsphere stock solution, adjust the stirrer speed to 500 to 800 rpm at 25°C and continue homogenizing for 30 minutes.

10. The preparation method according to claim 6, characterized in that, The specific implementation method of step S4 is as follows: use a 200 to 400 mesh screen with a screen tension set to 18 to 22 N / cm, and use a polyurethane squeegee to perform overprinting with a squeegee angle of 40 to 50 degrees and a downward pressure of 0.3 to 0.5 MPa. After printing, the product is placed in a continuous baking oven, with the baking temperature controlled at 120 to 150°C and the baking time at 3 to 5 minutes.